Análises para viabilização de corredores ecológicos e cumprimento de requisitos legais: subsídios à efetividade de área protegida e conservação de Mata Atlântica Setentrional - Rodrigues, Juliana Garcia Vidal (2017)
The Brazilian Atlantic Forest, currently only about 11.73% of its original vegetation, is one of the world's biodiversity hotspots, housing endangered animals and plants, great wealth and species endemism.The situation of fragmentation in which it finds itself is even more critical in its northern portion. Protected Areas, in particular Conservation Units (UCs), are the main forms of biodiversity conservation, through national and international efforts. In addition to the creation of PAs, the effectiveness of these areas is essential and, in case of extensive fragmentation, the creation of ecological corridors interconnecting protected areas to enable gene flow between species is relevant. Most UCs created in Brazil are not effective, and the difficulty in managing UCs constitutes a serious impediment to Conservation. In this scenario and in order to collaborate in the achievement of goals 11 and 12 of Aichi, as well as support one of the objectives of the National Plan of Action (NAP) for the Conservation of the Northeastern Atlantic Forest Herpetofauna, this study had as objectives , To analyze strategies for the implementation of viable public policies and instruments for the creation of ecological corridors in a protected area of the Northern Atlantic Forest; Analyze the fulfillment of legal requirements in favor of the creation and implementation of Conservation Unit in Atlantic Forest Northeastern; (PEMP) as a case study because it is one of the largest remnants of the Atlantic Forest in the RN, whose Management Plan provides for an ecological corridor area and, despite Created more than 10 years ago, has not yet been implemented. This is a qualitative study, whose data approach was divided into two complementary stages. At first, conceptual documentary analysis and observation of the PEMP was carried out as emblematic situation. For the interpretation of the data the argumentative analysis technique was used. In the categorization of the data we used arguments based on socio-environmental foundations, sustainable development and legal and environmental principles. For the analysis of the strategies to the corridor implementation, the idea of proposition was used, the laws being used as data and the juridical-environmental principles as guarantee. Also as a guarantee was adopted the exemplification of corridors planned for the PEMP. In a second moment, the emblem case was studied through documentary analysis, individual semi-structured interviews, focus group and participant observation during meetings of the Management Council in the years 2016 and 2017.1. It was found that the promotion of sustainable development as a way to conserve the Atlantic Forest is the essence of the law governing the biome - unique with a specific legal regime. It is fundamental to institute public policies that provide effectiveness to legal controls in order to prevent the succession of the degradation scenario of this biome, and to enable the increase of the existing percentage interconnecting its remnants. As for resource funds, their managers should pay attention to the Northern Atlantic Forest, reducing regional asymmetries in investments; The environmental agencies must elaborate projects for beneficiation. It was verified that the environmental agency fulfilled the requirements for the establishment of the PEMP, but the celerity compromised the result; The fulfillment of legal obligations with guarantee of its effectiveness, reduces the possible obstacles to the implementation of this CU; The occurrence of advances in the implementation of the UC due to judicial decision and ethical commitment of the Management Council and the Manager of the UC. The creation of created UC is a legal duty based on art. 2 of Law 6938/81 in art. 225 of the Federal Constitution - CF, in art. 4 of Law 9985/2000 and in the principle of prevention (implicitly enshrined in article 225, caput of the CF). It was also verified that the biggest problem for the lack of efficiency is structural, organizational of the Public Administration and the Judiciary, and the lack of prioritization in the political will. Obstacles encountered are common to the state NRCs. It is essential, urgent and fundamental that the environmental issue is seen and treated as an investment and not as an additional expense. Anthropocentric and exclusionary attitudes present a serious risk to the survival of humanity itself.